Facebook Commerce (F-Commerce) and French Women: A Gender Perspective - Mercanti-Guérin, Maria (European Journal of Economics and Business Studies, 2021)
The objective of this exploratory research is to investigate a mode of purchasing, social commerce and its main target, e-shoppers. Social commerce can take different forms: F-commerce, grouped purchases or discounts. Nevertheless, the best way to monetize social media remains the possibility to incite Internet users to promote the products or promotions obtained by their friends. Recommendations coming from friends are the main lever to create interactions between consumers, interactions centered on the purchase. However, many questions remain unanswered, especially regarding social acceptance and the real effectiveness of this type of promotion. In one study conducted on the "La Redoute" brand, we examined the extent to which our sample of women is likely to accept social shopping and, in particular, the product or service recommendations of their friends on their wall.
Keywords: social commerce, routes of persuasion, branding, recommendations, Facebook Commerce, F-commerce